Education and Management of Dysmenorrhea in Adolescent Girls with Turmeric and Tamarind as Complementary Therapy - Anggraeni Ayu Saputri (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
Dysmenorrhea is a health problem frequently experienced by women and can disrupt daily activities, especially on the first to third day of menstruation. Limited knowledge and experience regarding menstruation prevent many women from recognizing the causes and how to properly manage menstrual pain. Therefore, education is needed regarding the treatment of dysmenorrhea, including the use of complementary therapies such as consuming turmeric and tamarind as alternatives to help reduce menstrual pain. This study used a descriptive exploratory approach. The sample size was 30 female students from Doko 3 Blitar Junior High School, taken by accidental sampling. The instrument used was a questionnaire to measure knowledge. The results showed that 20 (67%) respondents had sufficient knowledge, 6 (20%) respondents had good knowledge, and 4 (13%) had poor knowledge. After being provided with education, there was an increase in good knowledge in 27 respondents (90%) and sufficient knowledge in 3 respondents (10%). This educational activity successfully increased the understanding and readiness of young women in managing dysmenorrhea pain through the application of non-pharmacological therapies.